Prevalence and determinants of asymptomatic Leishmania infection in HIV-infected individuals living within visceral leishmaniasis endemic areas of Bihar, India. - Raman Mahajan; Sophie I Owen; Shiril Kumar; Krishna Pandey; Shahwar Kazmi; Vikash Kumar; Emily R Adams; Amit Harshana; Sakib Burza (Public Library of Science (PLoS), 2022)
People living with HIV (PLHIV) have an increased risk of developing visceral leishmaniasis (VL) and poor outcomes compared to HIV negative individuals. Here, we aim to establish the prevalence and determinants of asymptomatic Leishmania infection (ALI) in a cohort of PLHIV in Bihar, India. We hoped to evaluate optimal diagnostic algorithms to detect ALI in PLHIV. We conducted a cross-sectional survey of PLHIV ≥18 years of age with no history or current diagnosis of VL or post kala-azar dermal leishmaniasis (PKDL) at anti-retroviral therapy centres within VL endemic districts of Bihar. ALI was defined as a positive rK39 enzyme-linked immunosorbent assay (ELISA), rK39 rapid diagnostic test (RDT) and/or quantitative polymerase chain reaction (qPCR). Additionally, the urinary Leishmania antigen ELISA was evaluated. Determinants for ALI were established using logistic regression and agreement between diagnostic tests calculated using Cohen's Kappa. A total of 1,296 PLHIV enrolled in HIV care, 694 (53.6%) of whom were female and a median age of 39 years (interquartile range 33-46), were included in the analysis. Baseline prevalence of ALI was 7.4% (n = 96). All 96 individuals were positive by rK39 ELISA, while 0.5% (n = 6) and 0.4% (n = 5) were positive by qPCR and rK39 RDT, respectively. Negligible or weak agreement was seen between assays. Independent risk factors for ALI were CD4 counts <100 (OR 3.1; 95% CI 1.2-7.6) and CD4 counts 100-199 (OR = 2.1;95% CI:1.1-4.0) compared to CD4 counts ≥300, and a household size ≥5 (OR = 1.9;95% CI:1.1-3.1). A total of 2.2% (n = 28) participants were positive by Leishmania antigen ELISA, detecting 20 additional participants to the asymptomatic cohort. Prevalence of ALI in PLHIV in VL endemic villages in Bihar was relatively high. Using the Leishmania antigen ELISA, prevalence increased to 9.0%. Patients with low CD4 counts and larger household size were found to have significantly higher risk of ALI. Trial Registration: Clinical Trial Registration CTRI/2017/03/008120.